Reducing anxiety of children in the dental clinic using film modeling - Maranan, Mona Lisa C.; Tordecilla, Maria Jennifer B. (2003)
The thesis investigated the effect of film modeling on the reduction of anxiety of children undergoing dental treatment. It specifically looked into the following: a0 differences in the fear attitude of children undergoing dental treatment; relation anxiety to the gender treatment that elicit high anxiety levels; whether the gender of the model affects the effectiveness of the film modeling. Forty children whose ages range from 49 months to 71 months old (4-5 years old) were selected in seven different preschools in Quezon City. Children were randomly assigned to control and experimental group using lottery. The experimental group viewed a 6-minute film modeling type of 5 year old model exhibiting positive behaviors during dental treatment. The control group, on the other hand was asked to draw pictures unrelated to the dental treatment for the same same interval. Three instruments were used in the study: a semi-structured questionnaire containing medical histories and previous dental experience, a behavioral profile rating scale which records the disruptive behavior during dental experience, a behavioral profile rating scale which records the disruptive during dental treatment and pulse rate which measure pulse rate activity during dental treatment procedure. The study also utilized four statistical procedures. T-test was used in determining the effect of film modeling on the reduction of anxiety in children undergoing dental treatment. This test was also used in determining the differences in the fear attitude of children undergoing dental treatment and the effect of the gender and age, Pearson product moment was used. Analysis of variance and Duncan's multiple range test were utilized to evaluate what stage/s in the dental treatment elicited high anxiety levels in children during treatment procedure. Findings from this study revealed that film modeling had a minimal effect on the reduction of anxiety of children during dental treatment. However, children who viewed the film modeling tape displayed fewer disruptive behaviors compared to the children who were asked to draw. Girls showed fewer disruptive behaviors compared to compared to boys. The gender of the model had an effect on children on the of the six stages of dental treatment: cleaning of upper teeth, cleaning of lower teeth and brushing of upper teeth. Reclining of the chair elicited the highest anxiety level in children during dental treatment. The study likewise revealed that anxiety is affected by the gender and age of the child. Girls exhibiting fewer disruptive behaviors showed low levels of anxiety during dental treatment. Younger children had higher levels of anxiety during cleaning of lower teeth. Based on the aforementioned findings, several recommendations were presented. Dentists should have a thorough understanding of children's cognitive skills and individual differences so that management of anxiety can be properly addressed. Educators, child developmentalists and curriculum planners are encouraged to incorporate the use of modeling as a teaching strategy in helping children acquire prosocial skills that would improve their self confidence. Parents are also encouraged to bring their children to the dentist as early as two years old so that they would be familiarized with the set-up of an dental clinic thus reducing their anxiety.
Thesis (M.F.L.C.D)--University of the Philippines, Diliman.
Keywords: Children -- Philippines -- Quezon City -- Preparation for dental care; Preschool children -- Dental care -- Philippines -- Quezon City